Bacterial communities of Antarctic lichens explored by gDNA and cDNA 16S rRNA gene amplicon sequencing. Issue 3 (7th February 2023) - Woltyńska, Aleksandra; Gawor, Jan; Olech, Maria A; Górniak, Dorota; Grzesiak, Jakub
Abstract: Recently, lichens came once more into the scientific spotlight due to their unique relations with prokaryotes. Several temperate region lichen species have been thoroughly explored in this regard yet, the information on Antarctic lichens and their associated bacteriobiomes is somewhat lacking. In this paper, we assessed the phylogenetic structure of the whole and active fractions of bacterial communities housed by Antarctic lichens growing in different environmental conditions by targeted 16S rRNA gene amplicon sequencing. Bacterial communities associated with lichens procured from a nitrogen enriched site were very distinct from the communities isolated from lichens of a nitrogen depleted site. The former were characterized by substantial contributions of Bacteroidetes phylum members and the elusive Armatimonadetes. At the nutrient-poor site the lichen-associated bacteriobiome structure was unique for each lichen species, with chlorolichens being occupied largely by Proteobacteria. Lichen species with a pronounced discrepancy in diversity between the whole and active fractions of their bacterial communities had the widest ecological amplitude, hinting that the nonactive part of the community is a reservoir of latent stress coping mechanisms. This is the first investigation to make use of targeted metatranscriptomics to infer the bacterial biodiversity in Antarctic lichens. Abstract : Habitat location and species-specific features shape the bacterial community structure in Antarctic lichens.